Effect of Cold Expansion on Fatigue Life of Hole Structure of TC17 Titanium Alloy - AI Yingjun; WANG Xin; SONG Yinggang; WANG Qiang; LUO Xuekun; TANG Zhihui; ZHAO Zhenye (Journal of Aeronautical Materials, 2017)
In order to improve the fatigue performance of TC17 central hole specimen, the hole wall surface integrity was characterized by scanning electron microscopy (SEM), roughness meter, X-ray diffraction, and the influence of hole cold expansion(HCE) parameter on the fatigue performance of the hole specimens was investigated. The results show that the minimum fatigue life (14718 cycle) of the HCE specimens with an expansion value of 0.18 mm is higher than the original specimen (13965 cycle). Compared to the specimens with the expansion values of 0.28 mm and 0.38 mm, the fatigue life dispersion is less, no obvious stress concentration phenomenon is found, and it has the best fatigue performance than the other two. The surface roughness value of hole wall is the lowest after the HCE with 0.18 mm, the inner hole wall forms a certain depth of strengthened layer, the residual compressive stress produced in the hole side effectively suppresses the produce of fatigue cracks in the inner hole wall, so the fatigue performance of hole structure is improved.